EFEKTIVITAS PENERAPAN TEORI BELAJAR ROBERT E SLAVIN PADA MATERI LOGIKA MATEMATIKA - Asmawati Aminuddin (Prodi Pendidikan Matematika Fakultas Keguruan dan Ilmu Pendidikan (FKIP) Universitas Muhammadiyah Parepare, 2025)
This study aims to investigate whether application of learning theory Robert E Slavin logic applied in mathematical learning in class XI student of MAN Sidenreng Rappang. This research is quasi-experimental study without control. And implemented the study comparing two treatments in two different groups, but only one type of behavior in a group that is learning with the application of learning theory Robert E Slavin. Samples of this study are all learners class XI MAN Sidenreng Rappang of 27 people. This study obtained data using research instruments purporting observation sheets and test the result. The data obtained in this study were analyzed by anlisis qualitative, descriptive statistical analysis. Qualitative results of the analysis show that there is a positive change in student attitude. The changes can be seen from many students who do dingpinkan activity and lack of activity that students who do not want at the time of the learning process. While the quantitative results of the analysis show that the learning outcomes of students showing good results. Case, we can see the value of the average size of 84.26 obtained from an ideal score of 100. In classical completeness of 100%. Based on the results of the analysis of data obtained, it can be drawn a conclusion that the theory of Robert E Slavin effective learning in learning logic applied mathematics in class XI student of MAN Sidenreng Rappang..